IDENTIFICATION OF SMOKED FISH PACKAGING SELECTION TO INCREASE SALES VALUE FOR SMOKED FISH PRODUCERS IN JAYAPURA CITY, PAPUA - Mantayborbir, Vyona; Indrayani, Ervina; Agamawan, Lalu Panji Imam; Manalu, Khristhoper Aris A. (Jurnal Perikanan Unram, 2025)
Smoked fish is a fish-based food product that is a leading product in Jayapura City, Papua. Most of the smoked fish demand in Jayapura City and surrounding districts is supplied from fish smoking centers in Hamadi and Imbi villages. The fish smoking technology used by producers, both in the fish smoking centers in Hamadi Village and the fish smoking centers in Imbi Village, is still relatively simple and unhygienic. Based on observations at smoked fish selling places, it was found that the average smoked fish trader sells their merchandise in an unpackaged condition. This makes the risk of contamination with pathogenic bacteria from the environment greater. The packaging materials used are also not able to protect smoked fish products from contamination that results in microbiological product damage. Common packaging materials used for smoked fish products are banana leaves, oil paper, and plastic bags. Based on the above problems, this study aims to determine how the packaging on smoked fish products in Jayapura City, Papua and how the role of packaging in improving the marketing of smoked fish products in Jayapura City, Papua. The tools and materials used in this research are stationery for writing, questionnaires for interviewing sources (business actors) and cameras for documentation. Data obtained from the field is presented in the form of pictures and analyzed securely. Keywords: Jayapura City, Labeling, Packaging, Smoked Fish, Vacuum.